Optimization of nutritional requirements for maximizing the mycelial growth and biomass production of Ophiocordyceps sinensis - S B, AKSHAYA; Krishnamoorthy, AS; Thiribhuvanamala, G; Pravin I, Arumuka; Priyadharshini, B (Mushroom Research, 2021)
Ophiocordyceps sinensis (ester while Cordyceps sinensis) an entomo-pathogenic fungus also known as Chinese caterpillar fungus is traditionally valued in Chinese medicine as it secretes lots of metabolites of pharmaceutical importance. However, this mushroom required diverse nutritional requirements for fast growth and maximum biomass production, and fruiting body development. In this regard, a study was initiated to test different carbon, nitrogen, minerals, vitamins, and chitin sources to enhance the growth and biomass production of O. sinensis under liquid fermentation. Among the carbon and nitrogen sources tested, sucrose (3%) and beef extract (0.5 %) showed maximum mycelial growth and biomass production (90.00 mm, 8.13g, and 8.17 g dry weight /L in 18 d). Also, the best mineral sources are K2 HPO4 and zinc chloride (0.2 %) that enhanced the maximum mycelial growth and biomass production (90.00mm, 8.20, and 8.12 g/L on 18 d respectively). Following this, the suitable vitamin (0.01 %) and chitin sources (0.1 %) like folic acid and dried powder of rhinoceros grub have enhanced the growth and biomass production of O. sinensis (90.00mm, 8.31, and 8.69 g/L on 18 d respectively). This study paves the way to enhance the metabolites secretion, biomass production, and fruiting induction of O. sinensis.